Quality comparison of sole from wild/farmed and closed/open circuits - Moraes, Karlos Ribeiro de (2012)
Soles (Solea spp) are a high-value commercial group of species with increasing importance in aquaculture. Common quality evaluation methods were used to compare Solea solea and Solea senegalensis sampled from the natural environment and fish farms. The aim was to develop a series of experiments and analysis of wild and farmed fish in Portugal, during 31 days, during boxed and iced storage. The analyses were performed using physical evaluations with Torrymeter type 295 and RT-Freshmeter type RT-2E, each 2 days and sensory evaluations using QIM (Quality Index Method), every day. The results show that farmed fish has a slower decrease in instrumentally-measured properties than the farmed, and QIM results show a loss in appearance more evident in the wild samples. For more accurate results, complementary analysis, like chemical, histological and microbiological, become necessary.